2014
DOI: 10.1002/ajh.23868
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2, randomized, double‐blind, placebo‐controlled study of siltuximab (anti‐IL‐6 mAb) and bortezomib versus bortezomib alone in patients with relapsed or refractory multiple myeloma

Abstract: We compared the safety and efficacy of siltuximab (S), an anti-interleukin-6 chimeric monoclonal antibody, plus bortezomib (B) with placebo (plc)+B in patients with relapsed/refractory multiple myeloma in a randomized phase II study. Siltuximab was given by 6 mg/kg IV every 2 weeks. On progression, B was discontinued and high-dose dexamethasone could be added to S/plc. Response and progression-free survival (PFS) were analyzed pre-dexamethasone by EBMT criteria. For the 281 randomized patients, median PFS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 31 publications
2
86
0
Order By: Relevance
“…Bortezomib monotherapy improved os significantly more than did dexamethasone (hr: 0.77, p = 0.003; and hr: 0.67, p = 0.47) 23,33 . No significant difference was seen with the administration of bortezomib before or after melphalan 17 or in combination with thalidomide, dexamethasone, or siltuximab 25,30,83 .…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Bortezomib monotherapy improved os significantly more than did dexamethasone (hr: 0.77, p = 0.003; and hr: 0.67, p = 0.47) 23,33 . No significant difference was seen with the administration of bortezomib before or after melphalan 17 or in combination with thalidomide, dexamethasone, or siltuximab 25,30,83 .…”
mentioning
confidence: 98%
“…Seven abstract publications of interim analyses of ongoing trials were also identified [79][80][81][82][83][84][85] . They are presented in Table i, but are not further discussed here.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In a large, randomized, phase 2 study of siltuximab in combination with bortezomib vs bortezomib alone in relapsed MM, an overall response rate ($PR) of 55% was seen with the combination as compared with 47% with single-agent bortezomib, but there was no improvement in progressionfree survival (PFS) with the addition of siltuximab (median PFS, 8.0 months vs 7.6 months). 20 This moderate additional activity of siltuximab in relapsed MM could be interpreted as advanced MM having become increasingly independent of the bone marrow microenvironment in general, and of IL-6 in particular, and left open the question of whether IL-6 blockade would be more relevant in newly diagnosed MM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of a randomized control trial in combination with bortezomib failed to report statistically significant differences in response rate, PFS, or OS, whereas it did increase the frequency of adverse events including cytopenias. [46][47][48] Currently it is being tested in patients with high-risk smoldering myeloma.…”
mentioning
confidence: 99%